Non‐Bonded Interactions Drive the Sub‐Picosecond Bilin Photoisomerization in the Pfr State of Phytochrome Cph1. Issue 3 (16th December 2015) - Yang, Yang; Heyne, Karsten; Mathies, Richard A.; Dasgupta, Jyotishman
Abstract: Phytochromes are protein‐based photoreceptors harboring a bilin‐based photoswitch in the active site. The timescale of photosignaling via C15 =C16 E‐to‐Z photoisomerization has been ambiguous in the far‐red‐absorbing Pfr state. Here we present a unified view of the structural events in phytochrome Cph1 post excitation with femtosecond precision, obtained via stimulated Raman and polarization‐resolved transient IR spectroscopy. We demonstrate that photoproduct formation occurs within 700 fs, determined by a two‐step partitioning process initiated by a planarization on the electronic excited state with a 300 fs time scale. The ultrafast isomerization timescale for Pfr ‐to‐Pr conversion highlights the active role of the nonbonding methyl–methyl clash initiating the reaction in the excited state. We envision that our results will motivate the synthesis of new artificial photoswitches with precisely tuned non‐bonded interactions for ultrafast response. Abstract : Two‐step photoswitching : Transient polarized IR and stimulated Raman spectroscopy studies demonstrate that sub‐picosecond photoisomerization of the bilin chromophore triggers Pfr ‐to‐Pr conformational signaling in phytochrome Cph1. The proposed mechanism could lead to new design criteria for engineering synthetic photoswitches.